To Prevent Oxidative Stress, What about Protoporphyrin IX, Biliverdin, and Bilirubin? - Ana Martínez; Isabel López-Rull; Juan A. Fargallo (MDPI AG, 2023)
The pigments responsible for eggshell color and patterning in birds are protoporphyrin IX (PP) and biliverdin (BV). Both are involved in the catalytic degradation of the hemo group. Bilirubin (BR), another pigment, is produced when BV is broken down. PP, BV, and BR are free radical scavengers. In this study, we theoretically investigated the antioxidant capacities of these three biological meaningful molecules using Density Functional Theory calculations. First, two antioxidant mechanisms were analyzed for PP, BV, and BR: electron transfer and Hydrogen Atom Transfer. Second, since PP and BV interact with the calcium carbonate matrix of the eggshell, we analyzed the interaction of these pigments with Ca2+ and investigated their chelate compounds. Third, we explored the pro-oxidant properties of PP and BV, which have been proposed for PP when photoactivated to the triplet state, but not for BV. Our results show that PP, BV, and BR are just as good antiradical as other important natural pigments (carotenoids). Neither the antiradical properties of PP and BV nor the UV-visible spectra change due to the presence of calcium, suggesting that the signaling function of these pigments is not affected by the link with Ca2+. Finally, we found that both PP and BV (alone and when linked to Ca2+) can transfer energy from its triplet state to molecular-oxygen-producing singlet oxygen, indicating their pro-oxidant capacity. This investigation answers important questions about the function of these pigments, which may help to understand their influence on the reproductive success of birds.